EFFECTS OF COATING WITH CHITOSAN FILM AND STORING AT DIFFERENT PERIODS OF BROOD BROILER EGGS ON HATCHING PERFORMANCE - Koseman, Abdurrahman; Akdemir, Fatih; Seker, Ibrahim (Pakistan Agricultural Scientists Forum, 2020)
The aim of this study was to investigate the effects of coating with chitosan film and storing at different times (from 7 days to 21 days) of Ross 308 brood broiler eggs on weight loss of the eggs and hatching performance. In this study, the experimental treatments consisted of three different storage periods (7, 14 and 21 days) and eggs of each of these groups were further divided in two sub groups as coating with chitosan film (group A, C and E) or not (group B, D and F). In total, six treatment groups were formed for the study. Total number of eggs used in the study was 1800. In all groups with chitosan coated, high early embryonic mortality (over 90%) and low mid and late embryonic mortality were observed (2.41%-6.89%) (p<0.05). The lowest hatchability was observed in groups A, C and E, which coated with chitosan film (0.67%, 3.00% and 0.33%, respectively). It was further observed that coating the fertilised broiler breeder eggs with chitosan film for different storage periods significantly decreased weight losses in the eggs, both during storage and incubation. However, the expected positive effects on hatchability of incubated eggs were not actually observed. Conversely, the coating of eggs with chitosan film adversely affected the embryonic mortality and the hatching performance.
Keywords: broiler; chitosan; hatchability; storage period